Enhancing Student Engagement and Cognitive Development Through Game-Based Learning (GBL) - Hikamah, Siti Roudlotul; Kusuma, Rani; Lestari, Putri Dwi; Ka-Lupae, Saenab (Universitas Negeri Malang, 2025)
Elementary school students are classified as playing-age children, they like to do activities while playing. This research aims to determine the influence of the Game-Based Learning (GBL) learning model on students' cognitive activities and abilities. This type of research is quasi-experimental, one-group pre-test and post-test design. The population of this study were Madrasah Ibtidaiyah students at Darussalam Seuksa School, Thepa, Southern Thailand. The research sample for grade 5 students was 28 students. Student activity is measured using an observation sheet with indicators measured using a 1-5 Likert scale. Cognitive abilities are measured by tests. The results of data analysis showed that the class average N-gain value was 0.73 for learning activities, and a value of 0.80 for student cognition. The N-gain value is 0.7 or g > 0.7, it can be concluded that the GBL model with effective interpretation is used, because it is in the high criteria. The results of the analysis of the percentage of student activity obtained a pre-test value of 47.11%, and the post-test obtained a value of 85.63%. The results of the cognitive percentage analysis obtained a pre-test value of 70.71% and the post-test value obtained a value of 94.0%. The results of the Wilcoxon test obtained a tailed asymp sig value of 0.00, meaning that there was a significant influence between the pre-test and post-test. GBL influences student activities and has a significant influence on student cognition.